WDEP Strategy for Increasing the Meaning of Life of High School Students - Kabri Kabri; Lubna Lubna; Eunike Rose Mita Lukiani; Pandu Adi Cakranegara; Dendi Pratama (AL-ISHLAH: Jurnal Pendidikan, 2023)
Meaning of Life is an important part of students' future where the problems in it are related to students' psychology and have an impact on their learning activities at school. The aim of this research is to find out whether the WDEP strategy is able to increase students' Meaning of Life. This research is quantitative research where data was obtained from class XII students. Data was collected using questionnaires, interviews and observations. After the data was obtained, the data was analyzed using a paired t-test. The results of this research show that the Wilcoxon test regarding increasing the Meaning of Life of students obtained a calculated Z value of -2.810 where the Asymp Sig (2-tailed) value was 0.00. These results indicate that the Asymp sig value is less than 0.05 (0.00 0.05). These results indicate an increase in students' Meaning of Life after receiving WDEP treatment. This shows that Ho is rejected and Ha is accepted. These results show that the WDEP strategy is able to increase students' Meaning of Life. With WDEP, students have clear goals, life satisfaction, freedom of will, self-control, and attitudes towards death and are able to have a reason to continue to exist.